Strategi Peningkatan Kesadaran Wisata Halal Terhadap Gen Z Dengan Mengoptimalisasikan Media Sosial - Kevin Julian Rifero; Setiaji Priambada; Tri Rezki Karuniawan; Raihan Mubarak Al-Luthfi (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2024)
This research is motivated by the lack of promotion of halal tourism on social media platforms. This causes a lack of interest in Generation Z in visiting halal tourism. It can be formulated in this study, increasing awareness of halal tourism to Generation Z can be increased by developing halal tourism information through social media, and presenting Influencers in it. The purpose of this research is to see how far social media affects Generation Z's interest in visiting halal tourism. This research uses Qualitative methods, with data collection techniques using questionnaires. Respondents collected were 50 with the Generation Z category. The results of this study show that the social media platforms Instagram and TikTok are the most widely used social media platforms by Generation Z. The role of influencers on social media is also very important. The role of influencers on social media also greatly influences Generation Z's visiting interest decisions in traveling. Increased promotion on social media through influencers is able to influence the increase in visiting interest of Generation Z in choosing halal tourist destinations.